2009
DOI: 10.1002/ppap.200930001
|View full text |Cite
|
Sign up to set email alerts
|

Structure Control in Reactively Sputtered Ag/Cu/(Mn)/O Films

Abstract: Copper‐ and silver‐based oxides were deposited on glass and silicon substrates by reactive sputtering in various Ar/O2 mixtures. The deposition conditions range for paramelaconite synthesis is discussed. The structure of silver oxide films is discussed as a function of the oxygen flow rate introduced into the deposition chamber. Ag/Cu/O films were deposited using either co‐sputtering of silver and copper targets or sputtering of composite targets (Ag50Cu50 and Ag60Cu40). The control of the oxygen and/or the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Pititjean et al [9] reported on the influence of annealing temperature on the decomposition, and structural and properties relationship in reactively sputtered Ag 2 Cu 2 O 3 films formed with Ag 50 Cu 50 sputter target. Pititjean et al [10][11][12] studied the effect of oxygen flow rate on the structure and properties of pulsed DC sputtered Ag-Cu-O films deposited using Ag 60 Cu 40 target. The effect of deposition temperature on the structural and optical properties of RF magnetron sputtered Ag 70 Cu 30 target was systematically studied [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pititjean et al [9] reported on the influence of annealing temperature on the decomposition, and structural and properties relationship in reactively sputtered Ag 2 Cu 2 O 3 films formed with Ag 50 Cu 50 sputter target. Pititjean et al [10][11][12] studied the effect of oxygen flow rate on the structure and properties of pulsed DC sputtered Ag-Cu-O films deposited using Ag 60 Cu 40 target. The effect of deposition temperature on the structural and optical properties of RF magnetron sputtered Ag 70 Cu 30 target was systematically studied [13].…”
Section: Introductionmentioning
confidence: 99%
“…The control of metal wettability through limited oxidation was originally applied by the same authors for fabricating highly efficient FTCEs using two‐dimensional continuous AgO x films as thin as 6 nm . However, in spite of the promising initial results, the proposed method has critical problems associated to the metal oxidation, which must be solved before the process can be practically applied . The deposition of oxidized metals by reactive sputtering requires a precise control of their oxidation due to the high oxidation affinity of the metals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this process allows the preparation of films with different Ag/Cu atomic ratio 9. The effect of oxygen partial pressure 10–12, current applied to the sputter target 13 and annealing temperature 14 on the structural, electrical and optical properties of the silver–copper oxide films formed by reactive magnetron sputtering were studied. The excess of silver atoms in the deposited films compared to copper induced the synthesis of biphased coatings of metallic silver and silver–copper oxide films 13.…”
Section: Introductionmentioning
confidence: 99%